2015
DOI: 10.1007/s00705-015-2507-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of proinflammatory NF-κB signaling by ectromelia virus in RAW 264.7 murine macrophages

Abstract: Macrophages are antigen-presenting cells (APCs) that play a crucial role in the innate immune response and may be involved in both clearance and spread of viruses. Stimulation of macrophages via Toll-like receptors (TLRs) results in activation of nuclear factor κB (NF-κB) and synthesis of proinflammatory cytokines. In this work, we show modulation of proinflammatory NF-κB signaling by a member of the family Poxviridae, genus Orthopoxvirus--ectromelia virus (ECTV)--in RAW 264.7 murine macrophages. ECTV interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…First, we found that LPS-induced nuclear translocation of key transcription factors,such as NF-κB, IRF3 and IRF7 that control the transcription of cytokine and chemokine genes was impaired in ECTV-infected GM-BM. ECTV has been demonstrated to modulate NF-κB signaling pathway in other APCs [49], as well as in non-immune cells [5052]. Inhibition of NF-κB activation can be mediated by ECTV-encoded ankyrin/F-box proteins, such as EVM002, EVM005, EVM159 and EVM170 that impair IĸBα degradation [53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we found that LPS-induced nuclear translocation of key transcription factors,such as NF-κB, IRF3 and IRF7 that control the transcription of cytokine and chemokine genes was impaired in ECTV-infected GM-BM. ECTV has been demonstrated to modulate NF-κB signaling pathway in other APCs [49], as well as in non-immune cells [5052]. Inhibition of NF-κB activation can be mediated by ECTV-encoded ankyrin/F-box proteins, such as EVM002, EVM005, EVM159 and EVM170 that impair IĸBα degradation [53].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NF-κB activation can be mediated by ECTV-encoded ankyrin/F-box proteins, such as EVM002, EVM005, EVM159 and EVM170 that impair IĸBα degradation [53]. Moreover, ECTV encodes counterparts of the following VACV inhibitory proteins altering NF-κB signaling pathway: A46 that disrupts TLR and IL-1β signaling, B14 that targets the IκB kinase (IKK) complex, and N1 that probably acts upstream of IKK complex activation [49,51]. Interestingly, our studies revealed that p65 NF-κB is recruited to ECTV replication sites in GM-BM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex process of inflammatory response is initiated by innate immune system receptors, which recognize a lot of pathogens or damage signals and precisely regulate immune response. Cells expressing pathogen-recognition receptors (PRRs) are able to present pathogens, antigens and secrete cytokines and chemokines [3,4]. PRRs, such as toll-like receptors (TLRs), activate cellular signalling pathways that result in NF-κB translocating into nucleus, and lead to the production of inflammatory cytokines and chemokines, which directly contribute to inflammatory lesions and immune diseases [5].…”
Section: Introductionmentioning
confidence: 99%